Genetic islands in pome fruit pathogenic and non-pathogenic Erwinia species and related plasmids - Llop, Pablo (Frontiers in Microbiology, 2015)
New pathogenic bacteria species belonging to the genus Erwinia associated with pome fruit trees (Erwinia pyrifoliae, E. piriflorinigrans, E. uzenensis) have been increasingly described in the last years, and comparative analyses have found that all these species share several genetic characteristics. Studies at different level (whole genome comparison, virulence genes, plasmid content, etc.) show a high intraspecies homogeneity (i.e. among E. amylovora strains) and also abundant similarities appear between the different Erwinia species: presence of plasmids of similar size in the pathogenic species; high similarity in several genes associated with exopolysaccharide production and hence, with virulence, as well as in some other genes, in the chromosomes. Many genetic similarities have been observed also among some of the plasmids (and genomes) from the pathogenic species and E. tasmaniensis or E. billingiae, two epiphytic species on the same hosts. The amount of genetic material shared in this genus varies from individual genes to clusters, genomic islands and genetic material that even may constitute a whole plasmid. Recent research on evolution of erwinias point out the horizontal transfer acquisition of some genomic islands that were subsequently lost in some species and several pathogenic traits that are still present. How this common material has been obtained and is efficiently maintained in different species belonging to the same genus sharing a common ecological niche provides an idea of the origin and evolution of the pathogenic Erwinia and the interaction with nonpathogenic species present in the same niche, and the role of the genes that are conserved in all of them.